Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Prestasi Belajar PAI Siswa Kelas V di SDN 5 Pandan Wangi Kecamatan Jerowaru - Baitul Izzah (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
This research is motivated by the author's interest in the efforts of education teachers in improving the learning achievement of Islamic Religious Education students at SDN 5 Pandan Wangi. In this case, the author wants to know. 1) What efforts are made by Islamic Religious Education teachers in improving the learning achievement of Islamic Religious Education students in grade V at SDN 5 Pandan Wangi. 2) What are the supporting and inhibiting factors of Islamic Religious Education teachers' efforts in improving the learning achievement of Islamic Religious Education students in grade V at SDN 5 Panan Wangi. This type of research is a qualitative research with a descriptive analysis method, in the data collection process, the researcher uses observation, interview and documentation methods. The validity of the researcher's data uses triangulation techniques. Data analysis is carried out in three stages, namely from the results of observation, interviews and documentation. The informants in this study were the principal, Islamic Religious Education teachers, and fifth grade students. Based on the results of the study, it can be concluded that 1. The efforts of Islamic Religious Education teachers in improving the Islamic Religious Education learning achievement of students at SDN 5 Pandan Wangi, Jerowaru District, are as follows: a.) Holding games in class such as quizzes/questions and answers, b.) Conducting discussions, c.) Providing motivation, d.) The curriculum used is the Merdeka curriculum. 2. Supporting and Inhibiting Factors of Islamic Religious Education Teachers' Efforts in Improving the Islamic Religious Education Learning Achievement of Fifth Grade Students at SDN 5 Pandan Wangi, a.) supporting factors: 1. The existence of training provided by schools, both government agencies and other independent institutions to teachers at SDN 5 Pandan Wangi, 2. Having learning facilities, 3. Providing cross-curriculum. b.) inhibiting factors: 1. Coming from the teachers themselves 2. Lack of Islamic Religious Education lesson hours.